Research on the anti-pull performance of a novel small-diameter steel tube-stud grouting connector - Ming-su Zhou; En-he Bao; Cheng-jun Luo; Jian-fa Wang; Yong-song Wu; Chang-jian Xiao (PLoS ONE, 2026)
To clarify the pull-out performance of steel tube-stud grouting (STG) connectors, this paper designed 18 test specimens, with main research parameters including embedment depth of stud (4d and 8d), steel type of stud, steel tube thickness, stud end diameter, and steel tube backing plate hole diameter. The study investigated the failure mode and deformation capacity of connectors, and strain patterns of the studs and steel tubes in the connectors, through pull-out tests and numerical simulation analysis. The study found a high degree of consistency between experimental and simulated results, and strain and stress in the studs gradually increased from the ends outward. This study fills an existing research gap regarding external-wall connections for steel structures and proposes an innovative, reliable connecting detail for prefabricated steel facade joints. Test results confirm that the proposed connection exhibits favourable pullout behaviour even with low-strength grout and a shallow stud embedment of 4d, which reduces material costs and simplifies field construction. The derived formula for yield load capacity achieves high prediction accuracy (maximum error is 11.3%) and applies to practical engineering calculations, thereby enhancing design efficiency and structural safety. In addition, this work provides theoretical underpinnings and experimental datasets for parametric optimization, engineering popularization, and the development of specifications for STG connectors.